Tanggung Jawab Korporasi terhadap Korban Kejahatan Tindak Pidana Lingkungan Hidup - Yusrizal Yusrizal (Universitas Syiah Kuala, 2012)
ABSTRACT: The concept of corporate responsibility is part of social and moral responsibility for actions and business activities that menpunyai influence on certain people, communities and the environment in which it operates can be accounted for in accordance with the provisions of Article 74 of Law Number 40 Year 2007 concerning Limited Liability Companies and Law Number 32 Year 2009 on the Protection of Environmental Management, especially in Article 87 and 116. The article clearly stated that the corporation is a crime that could potentially damage the environment and causing insured losses and casualties could be criminal. Both laws are still looking for corporate actors, so that victims are often overlooked corporation. The Liability of Corporate Towards the Victims of Environmental Crime